The Influence of Cutting Methods and Feed Rate on Dimensional Accuracy and Surface Roughness of HMR Panel - Rahmat, Bahtiar; Widiyanto, Wahyu; Purwanto, Agung Ari; Fahrudin, Muhammad (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2025)
This study investigates the influence of cutting methods and feed rates on the dimensional accuracy and surface roughness of HMR (High Moisture Resistance) panels. The aim is to determine the optimal cutting parameters that yield precise dimensions and smooth surfaces in CNC machining. Two cutting methods—single and double passes—were applied using feed rates of 2, 4, and 6 m/min. Dimensional accuracy was measured using a digital caliper, while surface roughness was evaluated with a surface tester. The results indicate that the double-pass cutting method significantly improves both dimensional accuracy and surface finish. Statistical analysis using ANOVA revealed that feed rate has a significant effect on surface roughness (p < 0.05), whereas dimensional accuracy is primarily influenced by the cutting method. These findings provide practical insights for optimizing CNC machining processes in furniture manufacturing using HMR panels.